Circadian Metabolism: What's new in circadian regulation of metabolism - LI Mindian; ZHANG Jianxin; ZHANG Jianxin (陆军军医大学学报)
Metabolic diseases, including obesity and diabetes, etc., are a spectrum of life-threatening diseases, in which metabolic dysfunction is a hallmark. It is in urgent need of new insights for the prevention and treatment of the diseases. Circadian rhythm is fundamental in health and wellbeing. Research on circadian rhythm has shed light on metabolic homeostasis, thereby giving birth to a new direction, named circadian metabolism. Here, we summarize recent advances in circadian metabolism regarding organelle regulation, inter- and intra-organ crosstalk of circadian clocks, as well as molecular mechanisms of time-restricted eating, and propose circadian communication across the hierarchy of central and peripheral clocks as a key concept for understanding the temporal regulation of metabolism. The underlying mechanisms on circadian communication should shed light on precision medicine in a temporal resolution and provide guidelines on when to eat and when to exercise for the prevention of metabolic diseases.